2001
DOI: 10.1164/ajrccm.163.1.9911120
|View full text |Cite
|
Sign up to set email alerts
|

Propofol versus Midazolam Regarding Their Antioxidant Activities

Abstract: Propofol and midazolam are commonly used as sedatives for critically ill patients. These patients usually suffer from the pathologic effects of oxidative stress, predominantly caused by an imbalance between the generation of reactive oxygen species and the antioxidant defense system. Therefore, the antioxidant activities of propofol and midazolam may be of clinical importance. We investigated the activities of these two sedatives against hydrophilic or lipophilic peroxyl radicals in a homogeneous solution and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
33
0
3

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(43 citation statements)
references
References 34 publications
6
33
0
3
Order By: Relevance
“…These patients usually suffer from the pathologic effects of oxidative stress, predominantly caused an imbalance between the generation of reactive oxygen species (ROS) and antioxidant defence system. 2) ROS are formed and degraded by all aerobic organisms. ROS can readily react with most biomolecules including protein lipids and lipoproteins and DNA.…”
mentioning
confidence: 99%
“…These patients usually suffer from the pathologic effects of oxidative stress, predominantly caused an imbalance between the generation of reactive oxygen species (ROS) and antioxidant defence system. 2) ROS are formed and degraded by all aerobic organisms. ROS can readily react with most biomolecules including protein lipids and lipoproteins and DNA.…”
mentioning
confidence: 99%
“…The effects of anesthetic agents on microcirculation are specifi c and dose dependent. The mechanisms that cause this interaction may be associated with oxidative disorders that occur during or after various anesthetic procedures (18)(19)(20).…”
Section: Discussionmentioning
confidence: 99%
“…These comparative results almost agree with previous studies. 25,26 In peroxynitrite-induced lipid peroxidation, the relative antioxidant potency was lidocaine > bupivacaine > ropivacaine >> mepivacaine and prilocaine in amide-type drugs and tetracaine > benzocaine > procaine in ester-type drugs. Tetracaine was reported to inhibit the lipid peroxidation of mouse heart homogenates at 0.25 mM, while lidocaine showed no prominent effect.…”
Section: Measurement With Cell Model Membrane Systemmentioning
confidence: 99%
“…Although previous screenings suggested that certain anesthetics may be potent antioxidants, 26,28,29 only limited information is available regarding their comparative effects, and the employed analytical methods vary according to studies. Therefore, the proposed method was applied to various anesthetics for comparing their antioxidant activities on the same methodological basis (Fig.…”
Section: Evaluation Of Anesthetics Under Pathophysiological Model Conmentioning
confidence: 99%